If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12=3(7-y)
We move all terms to the left:
-12-(3(7-y))=0
We add all the numbers together, and all the variables
-(3(-1y+7))-12=0
We calculate terms in parentheses: -(3(-1y+7)), so:We get rid of parentheses
3(-1y+7)
We multiply parentheses
-3y+21
Back to the equation:
-(-3y+21)
3y-21-12=0
We add all the numbers together, and all the variables
3y-33=0
We move all terms containing y to the left, all other terms to the right
3y=33
y=33/3
y=11
| (x-4)-(x+7=8x | | 8n-2=6n-12 | | X2-10x=-21 | | 10(t+8)=120 | | 6(3z-1)-3(z+8)=8(z+1) | | 92+12=x | | C=0.10x+13.25 | | 6a=3a+24 | | 6(f-9)=-18 | | -48=12n | | 92-12=x | | 3x+20+5x+66=360 | | 5x+9=-4x-45 | | 8a=35+a | | 2(r+9)=36 | | X=5y+23 | | 6=-3{x+2} | | -6(t-2)-(t+8)=8 | | 18+6x=36x+48 | | 3x/10-3=12 | | 7x-5=3x-4+×+5 | | 9+5(x-1)=2-5(x-6) | | 12x-8x+2=12 | | -4=c/3 | | -7x-8=x-24 | | x+131=180 | | 12x-16=3x-4 | | 40x=50(x-1) | | 9+8x-9-5x+3 = 9+(8x-9)-5x+3 | | 2v-14=16 | | 2-b/3=2/5 | | 18-3xx=-2 |